PENGARUH LAMA FERMENTASI DAUN PISANG DALAM RANSUM TERHADAP EFISIENSI PENGGUNAAN PAKAN AYAM BROILER - Liwe, Hengkie; Bagau, B.; Imbar, M R. (Universitas Sam Ratulangi, 2014)
FERMENTATION PERIOD EFFECT OF BANANA LEAF IN RATION ON BROILER FEED EFFICIENCY. This study was done to evaluate the fermentation period effect of banana leaf in ration on broiler feed efficiency. Animals used in this study were sixty broilers (Hubbard strain) at the age of three week old. Research was conducted using completely randomized design involving four treatments with five replications in each treatment. Treatments used were as follows: Ration containing banana leaf without fermentation (R0), Ration containing banana leaf fermented at five days (R1), Ration containing banana leaf fermented at ten days (R2), and Ration containing banana leaf fermented at fifteen days (R3). Data were analyzed by variance analysis. Significantly difference treatment effects on variable measures were tested using honestly significant difference (HSD). Variables measured were feed consumption, average daily gain, and feed efficiency. Results showed that that treatments had significantly difference (P<0,01) on feed consumption, average daily gain and feed efficiency. It can be concluded that ration containing banana leaf fermented at ten days produce the best feed efficiency of broilers. Keyword : Fermented banana leaf, feed efficiency, broiler